Exchange current density, electrocatalytic activity and volcano curve for the hydrogen electrode reaction: theoretical analysis - Gennero, Maria Rosa (2012)
The use of the exchange current density as a parameter for the characterization of the electrocatalytic activity in the volcano curve for the hydrogen electrode reaction was critically analyzed from the point of view of its evaluation and its kinetic interpretation. The methods usually employed in its calculation were first described and then analyzed in order to interpret the different values obtained from the extrapolation of Tafel regions and from the evaluation of the equilibrium polarization resistance. It was demonstrated that the use of Butler-Volmer type equations is inadequate and instead a general expression is proposed, derived in the framework of the Volmer-Heyrovsky-Tafel mechanism. The method proposed for the evaluation of the exchange current density was illustrated with several examples, being the different behaviours analyzed and discussed.